The unexpected guest : a mystery - Osborne, Charles, 1927-; Christie, Agatha, 1890-1976. (New York : St. Martin's Minotaur, 1999)
Michael Starkwedder crashes his car, and after finding a dead man and a woman with a smoking gun in the nearest house while searching for help, discovers that not everything is as it seems.
A novelization of a play.
Keywords: Murder -- Scotland -- Fiction; Mystery fiction